Impact of ozone on circulating tight junction protein claudin 4 and claudin 5 in patients with asthma - Pureun-Haneul Lee; Min-Hyeok An; DaYeon Hwang; Byeong-Gon Kim; An-Soo Jang (Allergy asthma & respiratory disease, 2024)
Purpose: Claudins are a type of tight junction proteins in human endothelia and epithelia. Ozone brings about oxidative stress and lung inflammation in humans and experimental models. However, the impact of ozone on claudins in subjects with asthma remains poorly understood. The aim of this study was to find variations in the tight junction proteins claudin-4 and claudin-5 in subjects with asthma in relation to ambient ozone concentration. Methods: We previously recruited 50 patients with stable/exacerbated asthmatics and 25 controls. Furthermore, to examine the influence of ozone concentration, we reanalyzed 18 patients with stable or exacerbated asthma and 3 controls. The plasma claudin-4 and claudin-5 levels in response to high concentrations of ozone were compared to stable/exacerbated asthma, and controls. Results: The lung functions were significantly lower in subjects with asthma than those in controls. Blood eosinophil proportions were significantly higher in exacerbated asthmatics than in subjects with stable asthma. In high concentration period of ozone, plasma claudin-4 levels were significantly higher in subjects with exacerbated asthma (0.44±0.30 ng/mL, P= 0.005) or stable asthma (0.38±0.31 ng/mL, P= 0.009) compared to those in control subjects (0.16±0.1 ng/mL). Plasma claudin-5 levels were lower in subjects with stable asthma (2.97±1.38 ng/mL, P= 0.011) than in control subjects (6.92±3.9 ng/mL), and higher in subjects with exacerbated asthma (7.49±4.23 ng/mL, P< 0.001) than those with stable asthma. Conclusion: These results reveal that claudins be changed in patients with asthma following ozone exposure in subjects with asthma.